2006
DOI: 10.1093/jee/99.6.1936
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Dynamics of Overwintering Homalodisca coagulata (Hemiptera: Cicadellidae)

Abstract: A 4-yr landscape-scale study was conducted to investigate spatial and temporal dynamics of overwintering Homalodisca coagulata (Say) (Hemiptera: Cicadellidae) in the lower San Joaquin Valley, California. Spatial structures of H. coagulata distributions were characterized with Moran's I index, and spatial associations between H. coagulata and the surrounding environment were investigated with a geographic information system. H. coagulata was caught consistently with sticky traps throughout the winter, and trap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…This species overwinters as adults (Turner and Pollard 1959), and during that period, a majority of the females seem to be reproductively inactive (Hummel et al 2006). During winter, however, the adults feed and ßy during warm conditions (Pollard and Kaloostian 1961, Blua and Morgan 2003, Almeida et al 2005, Park et al 2006. Therefore, if feeding of H. vitripennis adults is inßuenced by temperature conditions, the prevailing low winter temperatures of speciÞc areas in northern and central California may limit feeding activity, which would further increase overwintering mortality.…”
mentioning
confidence: 99%
“…This species overwinters as adults (Turner and Pollard 1959), and during that period, a majority of the females seem to be reproductively inactive (Hummel et al 2006). During winter, however, the adults feed and ßy during warm conditions (Pollard and Kaloostian 1961, Blua and Morgan 2003, Almeida et al 2005, Park et al 2006. Therefore, if feeding of H. vitripennis adults is inßuenced by temperature conditions, the prevailing low winter temperatures of speciÞc areas in northern and central California may limit feeding activity, which would further increase overwintering mortality.…”
mentioning
confidence: 99%
“…), and oleander had the highest H. vitripennis densities (Table 2). Previous reports of sticky trap catches in the General Beale area showed citrus, stone fruit (generally located near citrus groves), and table grape was the preferred H. vitripennis host before the areawide treatment program (Park et al 2006). Our Þndings show that some windbreak plant species (e.g., eucalyptus, jojoba) are serving as a host for residual H. vitripennis populations, especially when conditions in citrus are not favorable.…”
Section: Discussionmentioning
confidence: 47%
“…Our results are similar to those reported from the same San Joaquin Valley region. Park et al (2006) found 4.8 per trap per wk before areawide treatments in the General Beale region began (2000 Ð2001) and 0.04 H. vitripennis per sticky trap per wk after the areawide treatment program began (2001Ð2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent surveys in alfalfa showed trap location and Þeld quality impacted trap catch, with higher numbers of D. minerva caught when traps were placed in weedy sections of the Þelds . This is in contrast to the sharpshooters G. atropunctata and H. vitripennis that can be effectively monitored with yellow sticky traps (Goodwin and Purcell 1992, Park et al 2006. Sweep netting probably underreported the presence and numbers of D. minerva nymphs.…”
Section: Discussionmentioning
confidence: 94%